Perspective: enhancing economic evaluations and impacts of integrated pest management Farmer Field Schools (IPM‐FFS) in low‐income countries. Issue 11 (11th June 2020) - Rejesus, Roderick M; Jones, Michael S
Abstract: Over the last few decades, the use of Farmer Field Schools (FFS) have been considered one of the best approaches to disseminate integrated pest management (IPM) practices that aim to reduce reliance on and misuse of chemical pest control methods in agriculture. However, the published empirical literature has been decidedly mixed in terms of the effectiveness of the IPM‐FFS approach to improve economic outcomes in the short‐term (e.g. reduce chemical use, improve profits), and the potential for scaling‐up and IPM dissemination in the medium‐term. This article briefly explores the empirical IPM‐FFS literature and draws implications for future research directions that can potentially enhance IPM knowledge diffusion methods (including IPM‐FFS) and increase the economic impact of IPM techniques in low‐income countries. We find that promising research directions to improve understanding of IPM dissemination and IPM impacts will need to involve: (i) interdisciplinary long‐run studies using rigorous evaluation methods; (ii) in‐depth assessments of spillover effects; (iii) careful examination of IPM and IPM‐FFS impact heterogeneity; (iv) evaluation of novel IPM packages with herbicide‐ and genetics‐centered components; (v) piloting and impact assessments of alternative IPM knowledge diffusion structures; and (vi) piloting and impact analysis of IPM dissemination and learning programs with private sector involvement. © 2020 Society of Chemical Industry Abstract : This paper examines the empirical IPM‐FFS literature and draws implications for future research directions that can enhance the impact of IPM knowledge diffusion methods (including IPM‐FFS).